2007
DOI: 10.1002/art.22613
|View full text |Cite
|
Sign up to set email alerts
|

Daily health status registration (patient diary) in patients with rheumatoid arthritis: A comparison between personal digital assistant and paper‐pencil format

Abstract: Objective. The patient perspective workshops at the Outcome Measures in Rheumatology Clinical Trials have included daily measures of health status (patient diary) and use of electronic tools for data collection in the research agenda. The objective of this study was to compare daily and weekly registrations of self-reported health status measures between personal digital assistant (PDA) and paper-pencil (PP) format regarding scores, variation, and feasibility. Methods. Thirty-eight patients with stable rheumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 35 publications
4
32
0
3
Order By: Relevance
“…The selection of patients are described elsewhere [5]. Briefly, patients with stable disease between 25 and 79 years were recruited from the Oslo RA registry [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of patients are described elsewhere [5]. Briefly, patients with stable disease between 25 and 79 years were recruited from the Oslo RA registry [6].…”
Section: Methodsmentioning
confidence: 99%
“…In a recently published article we demonstrated that the fluctuations in self-reported health status measures were considerable, even in patients with stable disease [5]. This observation is of methodological interest for controlled clinical trials since patient-reported outcomes often are among primary endpoints and because parts of the within-patient variation will be included in the betweensubject variation.…”
Section: Introductionmentioning
confidence: 93%
“…Spørreskjemaer har bred anvendelse for å vurdere helserelatert livskvalitet 59,60 , og har vist seg å vaere sensitive for endring 61,62 , og selvrapportert tap av fysisk funksjon predikerer mortalitet 63 . Selvrapportering av helse kan foregå ved hjelp av elektroniske hjelpemidler 64,65 og det er utviklet grenser for hva som er viktig bedring 66 og grenser for hva pasientene synes er et akseptabelt nivå på plagene 67 . Konvensjonelle røntgenbilder er fortsatt standardmetoden for å vurdere tilstedevaerelse og endring i skjelettskade, og van der Heijdes modifisering av Sharp 3 score synes i dag å vaere mer brukt enn skå-ringssystemet som ble utviklet av Arvi Larsen og Knut Dale 68 .…”
Section: Sykdomsforløpet Og Effekt Av Behandling Vurderes Vedunclassified
“…Many studies (e.g., [9,11]), demonstrated the reliability of computerized questionnaires running on desktop and touchscreen computers with respect to their paper-based equivalents. Some researches also focused on the reliability of PDAs [3,4], tablets [10], and web-based forms [7]. Other studies were concerned with the acceptability of computerized questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies were concerned with the acceptability of computerized questionnaires. A preference for computerized versions over paperbased forms is illustrated in [3,12], while the usefulness of computerized questionnaires was obserbed in [2,7,10].…”
Section: Introductionmentioning
confidence: 99%